2009 International Symposium on Computer Network and Multimedia Technology 2009
DOI: 10.1109/cnmt.2009.5374579
|View full text |Cite
|
Sign up to set email alerts
|

Location-Aware Systems for Short-Range Wireless Networks

Abstract: Location-aware systems for short-range wireless networks, also called indoor positioning systems (IPSs), have become considerably popular in recent years with rapid evolution of ubiquitous computing and short-range wireless communications technologies. Much research and commercial IPSs have been developed and many of them have been applied or may soon be adopted in wide domains, like asset and people tracking, healthcare, manufacturing, safety, retail and shopping etc. In this paper, we present a layered conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…Similarly, studies comparing RTLS technologies can also be found in the literature [7][8][9][10][11][12][13]. Furthermore, a meta-review provides a comprehensive compilation of 62 survey papers on the topic of RTLS [14], and the classification of current typical RTLS is introduced with a layered conceptual framework [15]. Many technologies are available such as infrared light, ultrasound, laser and their combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies comparing RTLS technologies can also be found in the literature [7][8][9][10][11][12][13]. Furthermore, a meta-review provides a comprehensive compilation of 62 survey papers on the topic of RTLS [14], and the classification of current typical RTLS is introduced with a layered conceptual framework [15]. Many technologies are available such as infrared light, ultrasound, laser and their combinations.…”
Section: Introductionmentioning
confidence: 99%